Green Pea (Pisum sativum L.) Hull Polyphenol Extracts Ameliorate DSS-Induced Colitis through Keap1/Nrf2 Pathway and Gut Microbiota Modulation - Fanghua Guo (MDPI AG, 2021)
As a processing by-product, green pea hull (GPH) was found to be rich in phenolic components in our previous studies. In this study, UHPLC-LTQ-OrbiTrap-MS (Ultra performance liquid chromatography-linear ion trap orbitrap tandem mass spectrometry) technique was used to quantify polyphenols, and DSS (sodium dextran sulfate)-induced colitis mouse model was established to explore the effect of GPH extracts on colitis. The results showed that quercetin and its derivatives, kaempferol trihexanside and catechin and its derivatives were the main phenolic substances in the extract, reaching 2836.57, 1482.00 and 1339.91 µg quercetin/g GPH extract, respectively; GPH extracts can improved inflammatory status, repaired colonic function, regulated inflammatory factors, and restored oxidative balance in mice. Further, GPH extracts can activate Keap1-Nrf2-ARE signaling pathway, regulate downstream antioxidant protease and gut microbiota by increasing F/B value and promoting the growth of Lactobacillaceae and Lachnospiraceae, and improve the level of SCFAs (short-chain fatty acids) to relieve DSS-induced colitis in mice. Therefore, GPH may be a promising dietary resource for the treatment of ulcerative colitis.